Development of Differentiated E-LKPD Integrated with PjBL-STEM to Improve Students Science Literacy - Annisa Silfiyani; Agus Suyatna; Abdurrahman (Postgraduate, University of Mataram, 2024)
This study aims to test the effectiveness of integrated differentiated PjBl-STEM e-LKPD to improve science literacy. This research method uses the ADDIE R&D model. Classes IX.A, IX.B, IX.C, and IX.D at SMPN 1 Tanjung Bintang became the research sample with purposive sampling. The data analysis technique used the independent sample t-test and ANOVA. Based on expert validation, the percentage of content suitability aspects was 96.42%, construction suitability 96.25% and readability 90%. The average percentage of teacher responses to the content aspect was 95%, readability 93.75%, and attractiveness 98.75%, as well as the results of observations of learning implementation 77.4%, and reflection questionnaires with high criteria. In addition, the percentage of student responses to the readability aspect was 86.25% and attractiveness 90%. Based on these results, the developed e-LKPD is valid and practical with a very high category. The results of the t-test stated that there was a significant difference in the average scientific literacy of students between the control and experimental classes. The results of the ANOVA test stated that there was no effect of using e-LKPD with visual, kinesthetic, and auditory learning styles in improving scientific literacy because the e-LKPD developed had accommodated the needs of all students.